2020
DOI: 10.3390/agronomy11010066
|View full text |Cite
|
Sign up to set email alerts
|

Early Shoot Development Affects Carbohydrate Supply and Fruit Quality of Red-Fleshed Actinidia chinensis var. chinensis ‘Zes008’

Abstract: Fruit quality characteristics are highly variable across kiwifruit vines due to complex source-sink interactions. We investigated how variation in fruit quality of Actinidia chinensis (Planch.) var. chinensis ‘Zes008’ was influenced by different shoot types (short, medium or long) and rootstocks types (Actinidia chinensis (Planch.) var. deliciosa (A. Chev.) ‘Bruno’ or Actinidia macrosperma C.F. Liang). Short shoots had smaller leaves (−30 to −50%) and lower photosynthesis rates (−0.70 to −3.34 µmol m−2 s−1) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…This may be due to low photosynthetic rate which resulted in increase in leaf area with girdling at a rate of 25%. Present findings supported by Richardson et al (2021), who observed that girdling might create an imbalance in the source-sink ratios, transpiration rates, and structural properties of the leaves. Primary reasons for the decrease in the rate of photosynthesis that occurs after girdling are the closure of the stomatal aperture and the reduction in the amount of RuBP activity that occurs per leaf area Cheng et al (2008).…”
Section: Leaf Area and Carbohydrates Contentsupporting
confidence: 90%
“…This may be due to low photosynthetic rate which resulted in increase in leaf area with girdling at a rate of 25%. Present findings supported by Richardson et al (2021), who observed that girdling might create an imbalance in the source-sink ratios, transpiration rates, and structural properties of the leaves. Primary reasons for the decrease in the rate of photosynthesis that occurs after girdling are the closure of the stomatal aperture and the reduction in the amount of RuBP activity that occurs per leaf area Cheng et al (2008).…”
Section: Leaf Area and Carbohydrates Contentsupporting
confidence: 90%
“…chinensis 'Zes008' (red-fleshed kiwifruit) were also studied. These fruit were harvested from a commercial orchard based in Kerikeri New Zealand (for details see Richardson et al, 2021). During fruit growth these fruit were either bagged with lightproof bags (Hirst et al, 1990) from 56 days after anthesis (DAA) for 108 days or left unbagged (control).…”
Section: Materials and Data Collection Biological Samplesmentioning
confidence: 99%
“…chinensis 'Zes008' (red-eshed kiwifruit) were also studied. These fruit were harvested from a commercial orchard based in Kerikeri New Zealand (for details see [49]). During fruit growth these fruit were either bagged with lightproof bags [50] from 56 days after anthesis (DAA) for 108 days or left unbagged (control).…”
Section: Image Capturementioning
confidence: 99%